A Governance Framework for the Implementation and Operation of AI Applications in a University Hospital - Apfelbacher, Timo; Koçman, Sude Eda; Prokosch, Hans-Ulrich; Christoph, Jan (Digital Health and Informatics Innovations for Sustainable Health Care Systems. Proceedings of MIE 2024, 2024)
Background: Artificial intelligence (AI) is becoming increasingly important in everyday life and medical care with a notable gap between AI development in medicine there and its practical implementation in university hospitals. Objective: The aim was to develop a governance framework to guide the procurement and implementation of AI applications in university hospitals. Methods: Seven role-play expert interviews were conducted with interviewees from two university hospitals, simulating realistic AI system implementation scenarios. Results: A detailed governance framework was developed, divided into the sections general considerations, system selection criteria, and implementation. Further, a condensed version of the checklist was also derived. Conclusion: Many aspects of AI applications in medical care, such as the establishment of an AI board, remain, along with numerous concerns about the technology. These findings provide valuable insights into the topic.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Algorithms; Artificial Intelligence; Clinical; Expert Systems; Governance; Machine Learning; Physicians; Software; University Hospitals

Physicians' Attitudes Towards Artificial Intelligence: Results of the PEAK Project - Negash, Sarah; Gundlack, Jana; Buch, Charlotte; Apfelbacher, Timo; Christoph, Jan; Schildmann, Jan; Frese, Thomas; Mikolajczyk, Rafael (Digital Health and Informatics Innovations for Sustainable Health Care Systems. Proceedings of MIE 2024, 2024)
Artificial intelligence (AI) is rapidly reshaping the medical field. This study aimed to investigate the attitudes of physicians towards AI in medical care using focus groups. Most participants seemed to be open to the use of AI in medicine if transparency in AI systems is ensured, regulatory barriers are addressed and personal contact to the patient is maintained. This qualitative study allows insights into how German physicians perceive the use of AI in medical care. Gaining input from physicians is important when designing future applications of AI for the practical use in medical care.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Acceptance; Artificial Intelligence; Medical care; Perceptions; Physicians